Thermo-Mechanical Coupled Analysis of Electric Vehicle Drive Shafts - Kim, Se Eun; Jung, Chang Ho; Lee, Moon Gu; Han, Sangwon; Park, Jung Lyul; Jeon, Yongho (Applied Sciences (Switzerland), 2024)
With the growing concerns over global warming and abnormal weather patterns, the development of eco-friendly technologies has emerged as a critical research area in the transportation industry. In particular, the global automotive market, one of the most widely used sectors, has witnessed a surge in research on electric vehicles (EVs) in line with these trends. Compared to traditional internal combustion engine vehicles, EVs require components with high strength and durability to achieve optimal performance. This study focuses on the development of a constant velocity (CV) joint, a critical component for reliably transmitting the maximum output of an electric vehicle motor. Unlike conventional numerical methods, the proposed thermo-mechanical coupled analysis simultaneously accounts for thermal and mechanical interactions, providing more realistic operational performance predictions. This analysis, conducted using the thermal modules of Ls-Dyna and ANSYS Mechanical, effectively simulated field operation scenarios. Prototype testing under simulated conditions showed a 6% discrepancy compared to numerical predictions, validating the high accuracy and reliability of the proposed method. This robust thermo-mechanical coupled analysis is expected to improve the durability and reliability of CV joint designs, advancing electric vehicle component development.
Keywords: Constant velocity joint; Coupled analysis; Critical researches; Eco-friendly technologies; Electric vehicle drive; Element method; LS-DYNA; Thermo-mechanical coupled; Thermo-mechanical coupled analyze; Weather patterns; constant velocity joint; electric vehicle; finite element method; Ls-Dyna; thermo-mechanical coupled analysis